Los Márgenes del Archivo Arqueológico Andino: Espacios Locales y Ciencia Moderna en el archivo de Hans Heinrich Brüning - Walther Maradiegue (Nuevo mundo - Mundos Nuevos, 2023)
In this paper, I argue that the beginnings of modern archaeology in the Andes entailed the transformation of the peasant and Indigenous spatialities of which pre-Columbian buildings were a part, a task for which looking at the margins of the visual archives produced during the first decades of the twentieth century is necessary. To this end, I analyze some little-studied records from the visual archive of German engineer Hans Heinrich Brüning (1848-1928) and offer new ways to expand our knowledge of his archive and thus enrich debates about the origins of modern Andean archaeology. Likewise, I incorporate several works that have looked at his life, his works, and his later influence, as well as perspectives from critical geography that analyze the division and control of space in contexts of early capitalism. In this way, I conclude by proposing some ideas for thinking about the origins of Andean archaeology as part of broader projects utilizing local regimes of spatiality. Including specific images from Brüning's expanded archive in our readings of the history of archaeology will provide access to the tensions of representation that emerged during the first decades of the twentieth century.